Medical Toxicology: Antidotes and Anecdotes - Marcus, Steven M. (Springer, 2017)
A collection of challenging and unusual cases from the author's extensive experience as a Medical Toxicologist, these cases demonstrate medical problem solving and differential diagnosis in action from the perspective of an experienced clinician. Written in an engaging style and giving a fascinating account of some complex cases from real practice, this book will provide a good supplementary learning text for graduate students or those at an early stage in their professional career.